¿Cuál es el input lingüístico al que se exponen los aprendices de inglés como lengua extranjera? Un estudio comparativo en el contexto mexicano - Hernández Méndez, Edith; Chi Canul, Hilario; Ortiz Martínez, Azucena (Colombian Applied Linguistics Journal, 2021)
This study was aimed at describing the language input to which English language learners from three different BA programs at a Southern Mexican university are exposed in the classroom and outside. We used a quantitative approach with a correlational scope, by means of a survey, to conduct the research; the interactionist and cognitive model of language acquisition proposed by Gass (2018) was adopted as our theoretical perspective. We found that most of the learners do not utilize other language input sources out of the classroom, and if they do, this is for very little time and frequency. Additionally, the sources used by both the instructors and the learners are not of an interactive nature. The factors which mediate the language input are type of text (oral vs. written), saliency of the language forms, the previous knowledge, social distance, motivation, attitudes, and the attention. We add another filter: human or non-human sources; oral interaction with humans is the least source of input reported, and this can be a matter of personality or emotions triggered by an oral exchange with native speakers. As to the level, the students from the beginning and intermediate courses seem more motivated to expose themselves to extramural activities.